1995
DOI: 10.1007/bf01499140
|View full text |Cite
|
Sign up to set email alerts
|

Inducing jurors to disregard inadmissible evidence: A legal explanation does not help.

Abstract: Three experiments investigated mock jurors' ability to disregard inadmissible prior conviction evidence and hearsay. In Experiments 1 and 2, college students listened to an audiotape enacting a theft trial. The critical evidence favored the prosecution and was objected to by the defense. In three different conditions the judge either ruled the evidence admissible, ruled it inadmissible, or ruled it inadmissible and explained the legal basis for the ruling. In a fourth condition no critical evidence was present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 12 publications
4
61
0
Order By: Relevance
“…The effectiveness of multiple retractions after strong encoding of misinformation does not support concerns that multiple retractions could enhance continued influence by increasing familiarity of the misinformation Skurnik et al, 2005; see also Hintzman, 2010). It follows that the so-called backfire effects of retractions (Nyhan & Reifler, 2010;Pickel, 1995) may apply primarily to areas such as political beliefs or judicial settings, in which preexisting attitudes play a more important role for behavior.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effectiveness of multiple retractions after strong encoding of misinformation does not support concerns that multiple retractions could enhance continued influence by increasing familiarity of the misinformation Skurnik et al, 2005; see also Hintzman, 2010). It follows that the so-called backfire effects of retractions (Nyhan & Reifler, 2010;Pickel, 1995) may apply primarily to areas such as political beliefs or judicial settings, in which preexisting attitudes play a more important role for behavior.…”
Section: Discussionmentioning
confidence: 95%
“…In other words, the retraction could serve as a recursive reminder of the misinformation (Hintzman, 2010). Such backfire effects of retractions have been observed in examinations of the effects of retractions on political misperceptions (Nyhan & Reifler, 2010) and mock juror behavior (Pickel, 1995), and are obviously a reason for concern.…”
mentioning
confidence: 92%
“…In one such study, Petty and Wegener (1994) found that rating the desirability of taking a vacation in a desirable holiday destination lowered subsequent evaluations of taking a vacation in a nonholiday destination. Evidence that invalidated information may continue to contaminate future judgments is well established in testimony research where several authors have found that inadmissible evidence given during a trial continues to contaminate judgments after participants are instructed to ignore the information (Pickel, 1995;Schul & Manzury, 1990;Sommers & Kassin, 2001).…”
Section: Asymmetric Affective Perseverancementioning
confidence: 98%
“…Thus, even if the education is effective in addressing the first two steps, people may still not be able to detect the magnitude of the bias or know how to adjust their response to compensate for it. In courtroom research, for example, people find it difficult to disregard material that they have been instructed to ignore (Kassin & Sommers, 1997;Pickel, 1995;Sue, Smith, & Caldwell, 1973). The idea is that the judge"s instructions to disregard produce a "backfire effect" (Cox & Tanford, 1989) whereby individuals pay more attention to the evidence than if the judge had said nothing regarding the evidence.…”
Section: Why Education Alone Might Not Change Individuals' Social Judmentioning
confidence: 99%